Introducing genetics - Thomas, Alison (Of Anglia Ruskin University)
"The new edition of Introducing Genetics is a clear, concise, and accessible guide to inheritance and variation in individuals and populations. It first establishes the principles of Mendelian inheritance and the nature of chromosomes, before tackling quantitative and population genetics. The final three chapters introduce the molecular mechanisms that underlie genetics, including the techniques responsible for the current genetic revolution. As genetics affects all living organisms, examples are taken from insects, plants, animals, and humans. Each chapter ends with a set of problems to help the reader develop their understanding of genetics"--